The Reality Of Multiple Victims In Case Revenge Porn - Abdul Munir; Panca Setyo Prihatin; Wulan Junaini (UIR Press, 2021)
This paper describes the suffering experienced by a woman as a double victim of revenge porn. Indeed, revenge porn is a crime in the Pornography Law which has criminal sanctions in accordance with Article 4 paragraph (1) jo. Article 29, with the threat of imprisonment for a minimum of 6 months and a maximum of 12 years and a fine of between 250 million and/or 1 billion. By using an exploratory qualitative approach to the main subject, Bunga (21 years old) is not her real name, as a student at one of the universities in Pekanbaru, this study also uses the Feminism and Victim theory approach as the analytical knife. From the research findings, it can be concluded that the victim experiences multiple and varied sufferings from the revenge porn she experienced. Personally, the victim experienced sexual violence and extortion. In other cases, the legal process as a victim's right which can actually be taken to ensnare the perpetrator is not supported by the family with the aim that the perpetrator and victim can be united in the marriage bond. Meanwhile, socially, the victim gets a negative image and stigma in the form of reproach (cheap and immoral women) from the circle of friends and the environment where the victim lives, regardless of the perpetrator as the main actor in the revenge porn case.